2018
DOI: 10.1248/bpb.b17-00969
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Growth Differentiation Factor 15 in Skeletal Muscle of Old Taurine Transporter Knockout Mouse

Abstract: It has been identified that skeletal muscle is an endocrine tissue. Since skeletal muscle aging affects not only to muscle strength and function but to systemic aging and lifespan, myokines secreted from skeletal muscle may be crucial factors for intertissue communication during aging. In the present study, we investigated the expression of myokines associated with skeletal muscle aging in taurine transporter knockout (TauTKO) mice, which exhibit the accelerated skeletal muscle aging. Among transforming growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…As it is known that strenuous exercise induces GDF15 expression (20)(21)(22), it has been hypothesized that also skeletal muscle can be a source of this cytokine. Accordingly, GDF15 is expressed in muscles from mouse models of aging and inactivity (12,14). However, this idea has been recently challenged, as the concentrations of GDF15 during a physical exercise resulted similar in arterial and venous blood across the exercised leg (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is known that strenuous exercise induces GDF15 expression (20)(21)(22), it has been hypothesized that also skeletal muscle can be a source of this cytokine. Accordingly, GDF15 is expressed in muscles from mouse models of aging and inactivity (12,14). However, this idea has been recently challenged, as the concentrations of GDF15 during a physical exercise resulted similar in arterial and venous blood across the exercised leg (22).…”
Section: Discussionmentioning
confidence: 99%
“…As far as muscle atrophy and sarcopenia, there is debate on whether GDF15 is to be considered protective or detrimental. Recent data from animal models showed that GDF15 is able to induce muscle fiber apoptosis (12,13), but also the ablation of GDF15 resulted in an amplified skeletal muscle post exercise stress response, with a bigger increase of markers of muscle stress (Atf3, Atf6, and Xbp1s) (14). In humans, circulating GDF15 levels are significantly higher in subjects with sarcopenia or muscle atrophy (15)(16)(17) with respect to healthy subjects of comparable age.…”
Section: Introductionmentioning
confidence: 99%
“…9 GDF15 is also produced by skeletal muscle cells in response to aging-related stress, mitochondrial dysfunction and mitochondrial proteotoxic stress. [10][11][12][13] GDF15 is a useful diagnostic biomarker for mitochondrial diseases, which are caused by mitochondrial or nuclear genomic mutations. 10,11 Mitochondrial dysfunction, along with increased reactive oxygen species generation may result in increased blood GDF15 levels in patients with mitochondrial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…GDF15 is highly expressed in cardiomyocytes, adipocytes, macrophages, endothelial cells and vascular smooth muscle cells in pathological conditions such as inflammation, insulin resistance and oxidative stress 9 . GDF15 is also produced by skeletal muscle cells in response to aging‐related stress, mitochondrial dysfunction and mitochondrial proteotoxic stress 10–13 . GDF15 is a useful diagnostic biomarker for mitochondrial diseases, which are caused by mitochondrial or nuclear genomic mutations 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, levels of GDF-15 detected in blood plasma increased with time over a 7 day period of ICU stay, alongside a simultaneous and significant decline in muscle strength score and CSA of the rectus femoris for those with ICUAW [ 205 ]; this trend was not seen in the non-ICUAW group [ 205 ]. Since GDF-15 appears to play a role in numerous other pathological conditions, such as cancer and sarcopenia [ 206 ], further investigation of the GDF-15 influence in different cell types and disease conditions is warranted. Importantly, these findings offer proof-of-principle that blood-borne mediators may act as biomarkers and drug targets for new therapeutic interventions.…”
Section: Knowledge Gaps and Avenues To New Insightsmentioning
confidence: 99%